IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN MUTU SEKOLAH DI SD HJ. ISRIATI BAITURRAHMAN 1 SEMARANG - Martin Sitepu Martin; Yovitha Yuliejantiningsih; Rosalina Br. Ginting (STKIP Subang, 2023)
The focus of this research is principal academic supervision in improving the quality of SD Hj. Isriati Baiturrahman 1 Semarang. The aims of this research are inline with the sub-focuses: to describe the planning of academic supervision in improving the quality of SD Hj. Isriati Baiturrahman 1 Semarang, describe the implementation of academic supervision in improving the quality of SD Hj. Isriati Baiturrahman 1 Semarang, describe the evaluation of academic supervision in improving the quality of SD Hj. Isriati Baiturrahman 1 Semarang and describe the follow-up to academic supervision in improving the quality of SD Hj. Isriati Baiturrahman 1 Semarang. This research uses a qualitative method with a descriptive approach. Data collection techniques include interviews, observation, and document search. The data analysis is taken through the process of data condensation, data presentation and drawing conclusions. Test the validity of the data using the credibility test, triangulation, and confirmability. Based on the results of the study, the conclusions can be drawn: planning for academic supervision is carried out by the principal together with the supervision team, the implementation of academic supervision at SD Hj. Isriati Baiturrahman 1 Semarang consists of three activities, namely supervision of learning tools, learning processes, and assessment of learning through class visits, evaluation and follow-up academic supervision in the form of constructive reprimands, reinforcement and awards and implementation of technical guidance and further training. The academic supervision activities have been proven to be able to improve the quality of SD Hj. Isriati Baiturrahman 1 Semarang.